Enabling non-flammable Li-metal batteries via electrolyte functionalization and interface engineering. Issue 30 (15th July 2019) - Yu, Jing; Lyu, Yu-Qi; Liu, Jiapeng; Effat, Mohammed B.; Kwok, Stephen C. T.; Wu, Junxiong; Ciucci, Francesco
Abstract : A non-flammable CPE was developed and the assembled Li-metal batteries with an optimized interface deliver exceptional rate capability and stability. Abstract : Li-metal batteries (LMBs) with composite polymer electrolytes (CPEs) have attracted considerable attention compared with conventional Li-ion batteries. However, the uncontrolled Li deposition and the flammability of CPEs are still pressing issues. In this article, a non-flammable CPE is fabricated. The CPE consists of a poly(vinylidene fluoride) matrix, Li6.4 La3 Zr1.4 Ta0.6 O12 fillers, a flame-retardant trimethyl phosphate as the solvent, and a LiClO4 salt. It exhibits unique characteristics, including non-flammability, high ionic conductivity, flexibility, and good thermal stability. A fluoroethylene carbonate (FEC) additive is used on the surface of Li metal to facilitate the formation of a LiF-rich solid electrolyte interphase layer. The FEC-coated Li|CPE|LiFePO4 battery exhibits excellent cycling stability (at room temperature) with a discharge capacity of 152 mA h g −1 and nearly 100% coulombic efficiency over 500 cycles at 0.2C. The non-flammable CPE has a high rate capability of 109 mA h g −1 at 4C. To improve the energy density of the LMB, the LiFePO4 cathode is replaced with a high-voltage material LiNi1/3 Mn1/3 Co1/3 O2 . The obtained Li|CPE|LiNi1/3 Mn1/3 Co1/3 O2 cell exhibits a discharge capacity of 109 mA h g −1 after 100 cycles at 0.2C. Consequently, the strategy offers guidelines for the future development of safe batteries with high energy density.